Analysis Of Factors That Influence Employee Turnover Intention: PT. Anugrah Rekanan Abadi Mitra J&T Express - Thomas Nadeak; Muhammad Diaz Munandar; Neni Triana (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — This research aims to explain the factors behind employee turnover intention at PT. Anugrah Rekanan Abadi Partner J&T Express. Research method— The study employs a qualitative method, utilizing interviews, observation, and documentation, while verifying data validity through data triangulation. Informants include leadership and employees selected through purposive sampling. Result— The findings indicate that the factors influencing employee turnover intention at PT. Anugrah Rekanan Abadi Partner J&T Express are primarily economic factors and demographic factors. Conclusion— To address these issues, the company should consider reviewing the wage structure, providing clearer career development opportunities, and supporting education for young employees to foster a more stable work environment and reduce turnover intention.